Editorial: A Note on Theological Explorations in Time and Space - Mullins, R. T.; Anzalone, David; Page, Ben (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2021)
In 1969, T.F. Torrance published Space, Time, and Incarnation. This brought together recent work in philosophy and science on the nature of space and time in order to explore the implications for theology. Torrance’s theology engaged with the scientific thought of Albert Einstein and James Clerk Maxwell, as well as the temporal logic of A.N. Prior. The influence of this work on subsequent Christian theology cannot be overstated. Yet, a great deal has changed since 1969, and most contemporary discussions in systematic theology show little awareness of recent advancements in the metaphysics of time and space.